Comparison between Sadness and Happiness Conceptual Metaphors in the Songs of Parvin Etesami - Azadeh Sharifi moghadam; Maryam Azadikhah; Vahideh Abolhasani (زبان پژوهی, 2019)
The aim of this research was to study the conceptual metaphors of “sadness” and “happiness” as well as to compare them in the songs of the Iranian contemporary female poet, Parvin Etesami (1906-1941). In so doing, a number of 329 verses including at least one type of metaphors belonging to the domains of sadness and happiness were extracted and then were analyzed in terms of frequency and types. Lakoff, G. and M. Johnson’s (1980) conceptual metaphors as well as Kövecses’s (1986) list of metaphors associated with the mentioned emotions were selected and used as the theoretical framework. It was observed that metaphors of sadness were of higher frequency than metaphors of happiness (266 vs. 66 cases). The use of concepts associated with feeling of sadness like “orphans”, “loneliness”, “aging”, “opperession” and “injustice” in Parvin Etesami’s poetry is meaningful and suggests her deep understanding of social suffering in the society at that time. Also, analysis of the data showed that the two sets of metaphors are different, regarding semantic features as well as semantic diversity. The following source domains associated with the metaphors of the opposite types show the difference: -          Sadness is bitter vs. happiness is sweet. -          Sadness is a wicked person vs. happiness is a great man. -          Sadness is a dry plant vs. happiness is a green one. -          Sadness is night vs. happiness is daytime. -          Sadness is fall vs. happiness is spring -          Sadness is down and distant vs. happiness is up and adjacent. -          Sadness is tightness vs. happiness is openness. -          Sadness is destruction vs. happiness in construction. -          Sadness is a heavy burden. -          Sadness is a dangerous animal. -          Sadness is a natural disaster.   Besides, the two categories of metaphors show similarities of the following types: -          Sadness and happiness are physical substances. -          Sadness and happiness are animates. -          Sadness and happiness are directions. -          Sadness and happiness are locations. -          Sadness and happiness are time. -          Sadness and happiness are healthiness/illness. Also, it was found that there is a great conformity between the metahors extracted from the data and the universal list of metaphors of the same feelings.